Alterações da liberação do neurotransmissor ácido gama-aminobutírico (GABA) associadas à falta da distrofina no cerebelo do camundongo distrófico (mdx). Efeitos da modulação pré-sináptica nicotínica - Silva, Janyerson Dannys Pereira da [UNIFESP] (2016)
Dystrophin is a cytoplasmic protein expressed in striated muscles and at post-synaptic regions of neuronal synapses. In skeletal muscles, dystrophin is involved in the stabilization of the sarcolemma, in the regulation of nicotinic receptors (nAChR) and the motor end-plate morphology, as well as in intracellular signaling. Mutations in the dystrophin gene lead to a deficiency or expression of a non-functional protein, causing a degenerative, progressive and irreversible myopathy known as Duchenne muscular dystrophy (DMD). One third of DMD patients also present cognitive deficits that are non-progressive and unrelated to muscular disease. However, the role of dystrophin in the central nervous system (CNS) is not well established. Studies using dystrophin-deficient mice (mdx), a murine model of DMD, described a reduction in the number and size of GABAA receptors clusters in hippocampal and cerebellar neurons. Furthermore, the probability of spontaneous GABA release was increased in hippocampus, and reduced in the cerebellum of dystrophic mice. This work was aimed to evaluate the influence of dystrophin on the release and uptake of GABA in brain regions that express high concentrations of dystrophin, namely in the cerebral cortex (CTX), hippocampus (HPC) and cerebellum (CBL) of control and mdx mice. Analysis of [³H]-GABA outflow evoked by nicotinic stimulation or potassium depolarization, and kinetics analysis of GABA uptake were performed using synaptosomes isolated from all three brain regions of control and mdx mice. Synaptosomal samples from CTX, HPC, CBL were loaded with [³H]-GABA (40 nmol/L) and the radioactivity was quantified by ?-scintillation counting. The tritium outflow was expressed as fractional release (Fn). To determine nAChRs subtypes involved in the neurotransmitter release, the release of [³H]-GABA induced by selective agonists for ?2/?4- (5IA-85380) and ?7- (PNU-282987) containing nAChRs subunits were obtained in the absence and presence of antagonists of both nAChRs subtypes, dihydro-?-erythroidine (DH?E) and methyllycaconitine (MLA), respectively. Transmission electron micrographs of CTX, HPC and CBL synaptosomes did not reveal significant morphological or structural differences between control and mdx groups. The results obtained in neurotransmitter release assays showed that CBL was the most affected structure by dystrophin deficiency. The release of [³H]-GABA stimulated by nicotine (Nic, 10 ?mol/L) in these preparations was decreased by 47% in mdx compared to control values (Fn = 0.29 ± 0.06%, n=12). Nicotine-evoked [³H]-GABA release in CTX and HPC synaptosomes did not differ between control and mdx group. [³H]-GABA release evoked by potassium depolarization (KCl, 9 mM) of CTX, HPC and CBL synaptosomes did not differ between control and mdx group. Superfusion of DH?E (1 ?mol/L) decreased the nicotine-evoked [³H]-GABA release in CTX, HPC and CBL synaptosomes by 50-70%, in control, and by 55-95%, in mdx groups. In similar assays, MLA (10 nmol/L) produced a greater inhibition of the Nic-evoked [³H]-GABA release in CTX, HPC and CBL synaptosomes from control (80-99%) and mdx (73-85%) groups. The release of [³H]-GABA stimulated by 5IA-85380 (?4?2; 0.01 ?mol/L), or PNU-282987 (?7; 0.1 ?mol/L) were inhibited by equal concentrations of DH?E and MLA, respectively, indicating the involvement of both nAChRs subtypes in regulation of GABA release of all three brain regions. Kinetics analysis of [³H]-GABA uptake in cerebellar synaptosomes from mdx mice revealed a reduction of 50% in the t1/2 of maximal uptake (control: 1.24 ± 0.26 min) and an increase of 44% in Vmax (control: 982.0 ± 100.9 pmols/mg protein/min), with no alteration of the Km values. Kinetics parameters of GABA uptake determined in CTX and HPC did not differ between control and mdx group. The results show that dystrophin-deficiency in CBL of mdx mice caused a reduction in the GABA release stimulated by nAChRs activation, but not by KCl depolarization. This effect was consistent with the detected increased rate of [³H]-GABA uptake in synaptosomal samples, and the previously reported increase of GABA content in CBL homogenates of mdx mice (Frangiotti, 2015). The presented data along with the described altered release of [³H]-ACh induced by nAChRs activation in HPC synaptosomes of mdx mice (Parames et al., 2014) indicate that dystrophin absence affects the GABAergic and cholinergic neurotransmission in both brain structures. The impairment of neurotransmission in both brain regions involved in attention, memory and learning processes, as well as motor coordination functions may contribute to the cognitive deficits and behavioral disorders described in some DMD patients and in mdx mice.